If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 11x + 14 = 12x + 4 Reorder the terms: 14 + 11x = 12x + 4 Reorder the terms: 14 + 11x = 4 + 12x Solving 14 + 11x = 4 + 12x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-12x' to each side of the equation. 14 + 11x + -12x = 4 + 12x + -12x Combine like terms: 11x + -12x = -1x 14 + -1x = 4 + 12x + -12x Combine like terms: 12x + -12x = 0 14 + -1x = 4 + 0 14 + -1x = 4 Add '-14' to each side of the equation. 14 + -14 + -1x = 4 + -14 Combine like terms: 14 + -14 = 0 0 + -1x = 4 + -14 -1x = 4 + -14 Combine like terms: 4 + -14 = -10 -1x = -10 Divide each side by '-1'. x = 10 Simplifying x = 10
| -3.2+14.08=-4.8 | | -3x-7=-43 | | (6/7)^-2 | | 2(-2)-y=3 | | 4g-7(f+g)= | | 1+2+1/2+1/4(2)+3x=8+1/2 | | -7x-y=13 | | 15+40= | | 3x^3-16x^2+16x=0 | | -3x-7=43 | | 5=5(4)-23+2(4) | | 1/3-2/3 | | x+x+28+2x-33=587 | | 2x-2+5=x | | 25y^2+15y=-2 | | (4x-3)(x+7)=38x-9 | | 9m=5m-25 | | -4t+8= | | 6y=3+x | | 9n=4m-25 | | 3x+1=2(x+2) | | 3x-x^3=1.8 | | 5d+-2=14 | | 9b+4=8b | | x/4=25 | | 10y+3x=-12 | | -6(x-3)= | | x=1/4(3) | | 12x+15X=120 | | 1/3t=7 | | 6x^2+5xy+y^2=0 | | -7x+1=27 |